“Implementación de una máquina prototipo atemperadora que controle el proceso de cristalización del chocolate en la Asociación de Campesinos Lamanenses A.S.C.A.L.A” - Dias Cuchipe, Iralda Lizeth (2021)
This research is based on the design and implementation of a prototype machine for the crystallization of dark chocolate with milk, by using scientific references such as bibliographic records about the cacao cultivation around the whole wide world, the country, and the canton as well as it process of transformation into fine aroma chocolate. This project will contribute to the Campesinos Lamanenses Association "ASCALA". The AISI 304L steel was used for the elaboration of this prototype because that material provide better quality of work by avoiding contamination and corrosion in the production process. The implementation of the project helped to reduce the crystallization time of chocolate, so generating a notable decrease in the production process from four hours to two hours for each crystallization process, as well as determining the optimal temperatures for crystallization which range from a heating of 45° C to a cooling of 27° C, and a heating of 32º C again. The range allows to dilute chocolate completely, then to cool it in a controlled span; in addition, the final heating allows to crystallize the dark chocolate. Finally, the product is stored at a temperature lower than 25° C before being distributed. In this way, optimizing the human and economic resources that are used in the production of dark chocolate with milk.